Liquidity and Profitability: A Case of Insurance Companies in Nepal - Sitanggang, Eva RA; Koirala, Kamal Bahadur; Singh, Sanju Kumar (Jurnal Mebis, 2025)
This study's primary objective was to examine the impact of liquidity on the profitability of listed financial companies in Nepal. It aimed to understand the current liquidity and profitability status of these institutions. Using an economic methodology, specifically multivariate regression analysis, two regression models were developed to assess the effect of liquidity variables on profitability, measured by return on assets (ROA) and net profit margin (NPM). The research employed non-probability sampling techniques alongside a descriptive and informal comparative research approach. The study used two dependent variables (ROA and NPM) and five independent variables: the capital adequacy ratio (CAR), loan to total assets ratio (LTTAR), cash reserve ratio (CRR), credit to deposit ratio (CDR), and cash and bank balance to total deposit ratio (CBTDR). Ten distinct hypotheses were tested based on the regression analysis. The findings indicated that CDR, CBTDR, LTTAR, and CRR had a significant impact on ROA (p-values < 0.005), while CAR was found to be insignificant for ROA. For NPM, LTTAR demonstrated a substantial negative impact (p-value < 0.05), with other factors showing no significant effect. The overall regression models demonstrated fair explanatory power and statistical fit.